2022
DOI: 10.59874/001c.75017
|View full text |Cite
|
Sign up to set email alerts
|

What Is Helpful: The Client’s Perception of the Solution-Focused Brief Therapy Process by Level of Engagement 🇵🇱 🇷🇴

Abstract: The current study aimed to explore what elements from the solution-focused brief therapy (SFBT) process clients perceive as helpful and how their perception varies by level of engagement. The replication of the SFBT model from the perspective of clients residing outside the USA was also examined. A mixed-method design was used in a naturalistic setting in Poland. Clients (N = 346; 74% females) aged 18 to 67 attending psychotherapy in private practice were interviewed. Thematic analysis revealed eleven main the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The research concerned with the client's experience all indicated positive themes associated with the solution-focused process and the usefulness and benefits for the clients of solution-focused specific aspects (Hsu et al, 2022;Sagar & Özabaci, 2022;Turns et al, 2022;Żak, 2022). Thematic analyses revealed that clients experienced best hopes and exploring what works as useful elements (Firth & Tripathi, 2022), while having difficulties reacting to the miracle question (Turns et al, 2022).…”
Section: Effectiveness Of the Solution-focused Processmentioning
confidence: 97%
“…The research concerned with the client's experience all indicated positive themes associated with the solution-focused process and the usefulness and benefits for the clients of solution-focused specific aspects (Hsu et al, 2022;Sagar & Özabaci, 2022;Turns et al, 2022;Żak, 2022). Thematic analyses revealed that clients experienced best hopes and exploring what works as useful elements (Firth & Tripathi, 2022), while having difficulties reacting to the miracle question (Turns et al, 2022).…”
Section: Effectiveness Of the Solution-focused Processmentioning
confidence: 97%
“…Considering the concept of client engagement, a link is often drawn to the idea of levels of motivation for change, as identified within the transtheoretical model of change (TTM) proposed by Prochaska and DiClemente (1982;as cited in Prochaska et al, 2008). While the literature has discussed in greater detail some similarities between the levels of therapeutic engagement and the levels of client motivation (McFarland, 1995;Żak, 2022), the distinction here is important because neither de Shazer (1988) nor Isebaert (2016) intended the levels of engagement to reflect client motivation for change explicitly, but rather the type of relationship and engagement that the client is seeking from the practitioner and from therapy more broadly. This difference is typified further when considering the resulting implementation of the concepts.…”
Section: Psychotherapy and Counselling Journal Of Australiamentioning
confidence: 99%
“…While some similarities to associated concepts such as the TTM have already been addressed earlier in this paper, such models apply a more structured approach to increasing client motivation and readiness, thus lending themselves more to empirical studies. Some existing studies have explored the relationship between engagement levels and other associated solution-focused themes more generally, rather than specifically exploring the effectiveness of engagement levels themselves (Corcoran, 1997;Odell et al, 2005;Sharry & Owens, 2000;Żak, 2022). Given that further research into the effectiveness of the therapeutic engagement levels concept would be useful to the field, it is also acknowledged that the more flexible nature of the concept creates challenges in this sense.…”
Section: Consultantmentioning
confidence: 99%